Storytelling and the Italian public libraries - Galluzzi, Anna; Faggiolani, Chiara (Qualitative and Quantitative Methods in Libraries, 2019)
The transition from the so-called Evidence-based Librarianship (EBL) to the Narrative-based Librarianship (NBL) - in line with the "narrative turn" occurred in the social sciences and humanities - is taking places in Italy too. Starting from the acknowledgement that field surveys using narrative methods are increasing in the Italian public libraries, the paper presents the methodology and the first outcomes of a meta-research built upon a corpus encompassing the textual data produced by means of qualitative research techniques. Applying a software for automatic text analysis (IRaMuTeQ) and using both an inductive and a deductive approach, the authors analyse the lexicon behind the narratives of users, non-users, opinion leaders and staff members and chase various objectives. The result is a map of questions and answers that brings to light emerging research patterns and boosts further considerations about the chosen methodological approach.